Objective Clinical Assessment of Posture Patterns after Implant Breast Augmentation. Issue 2 (August 2015) - Nicoletti, Giovanni; Mandrini, Silvia; Finotti, Valentina; Dall'Angelo, Anna; Malovini, Alberto; Chierico, Simona; Faga, Angela; Dalla Toffola, Elena
<x xml:space="preserve">Abstract</x> Background: An increased weight of the breasts causes several spinal postural alterations that reduce the ability to perform dynamic tasks requiring a stable balance. The effects of the increased weight of the breasts on static posture after implant breast augmentation have not been investigated yet. Methods: Forty volunteer healthy women were asked to wear different sized breast implants (800, 400, and 300 g) inside a dedicated sports bra for 6½ consecutive hours during their everyday life activities, 1 day for every implant size. Posture changes were assessed with the association of a physiatric clinical examination with a static force platform analysis. Results: A significant increase in cervical lordosis after the use of 400-g breast implants and upward was demonstrated. This alteration was stable between the 400-g and 800-g breast implants. The 400-g (per breast) implant might therefore be the load threshold that breaks the cervical postural physiologic balance. A significant increase in lumbar lordosis was demonstrated only after the use of the 800-g breast implants. The static force platform assessment demonstrated a worsening of the balance independent from the visual control with the use of 400-g and 800-g implants. Conclusions: Heavy breast implants proved to induce reversible alterations in the spinal curve, and 400 g is the cutoff for functional physiologic compensation in the short term. Such a weight might be considered the safety limit for the use of breast implants for cosmetic purposes.